Effect of heat-treated flour on the quality and storage stability of fresh noodles. (July 2021) - Hong, Tingting; Zhao, Qiyan; Xu, Dan; Yuan, Yirong; Ma, Yue; Wu, Fengfeng; Xu, Xueming
Abstract: The effects of heat-treated flour on the quality, water distribution, and molecular weight distribution of protein and volatile compounds in fresh noodles during storage were evaluated. Heat-treated wheat flour (HTWF) at 80°C–100 °C for 30 min was used to prepare noodles (HTFN). Results showed that heat treatment improved the quality of the noodles during storage. Compared with the control samples, the HTFN samples had a lower total plate counts (TPCs), a lower mold and yeast counts (MYCs), and a more stable pH value during storage. Heat treatment provided fresh noodles with bright color and positive texture. Low-field nuclear magnetic resonance (LF-NMR) results indicated that heat treatment restricted water migration with high A21 and minimal T23 (less free water) in the HTFN samples. Heat treatment promoted the aggregation of protein molecules, further inducing a difference in the quality of noodles. Moreover, heat treatment decreased the relative concentrations of free radicals and improved the overall aroma profile. Highlights: Heat treatment extended shelf life of fresh noodles. Heat treatment restricted the water migration of fresh noodles during storage. Heat treatment promoted the aggregation of protein molecules in treated flour. Heat treatment decreased the relative concentrations of free radicals of fresh noodle. Heat treatment improved the overall aroma profile.